Plural Embodiment(s) of Mind. Genealogy and Guidelines for a Radically Embodied Approach to Mind and Consciousness - Ceruti, Mauro; Damiano, Luisa (Frontiers in Psychology, 2018)
This article focuses on a scientific approach to the study of cognition that Warren McCulloch introduced in the era of cybernetics as “experimental epistemology.” In line with recent attempts to highlight its contribution to cognitive science and AI, our article intends to draw attention to its unexplored influence on contemporary embodied approaches to the investigation of mind and consciousness. To this end, we will survey a series of models of cognitive systems genealogically related to the McCulloch-Pitts networks-based modeling approach, i.e., von Foerster’s model of the biological computer, the Maturana-Varela model of the autopoietic system, and Varela’s model of emergent selves. Based on examination of the relevant aspects of these models, we will argue that they offered the McCulloch-Pitts “cybernetic of networks” a coherent methodological and theoretical line of development, complementary to the well-known computationalist one. As we will show, this alternative evolutionary line empowered the biological orientation of McCulloch’s experimental epistemology, laying foundations for contemporary “radically embodied” approaches to mind and consciousness – in particular the Thompson-Varela approach. We will identify the heritage of this tradition of inquiry for future research in cognitive science and AI by proposing guidelines that synthetize how its methodological and theoretical insights suggest taking into account the role(s) played by the biological body in cognitive processes – consciousness included.